PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF LEARNING PADA MATA PELAJARAN IPA - Yuhana; M. Ashif Barkia; Nurma Kurnia; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
One of the competencies that must be possessed is the ability to think critically and problem solve. For this reason, critical thinking skills are very important to develop seeing from the low science achievement of students in Indonesia. The problem that often occurs in learning is that teachers do not provide opportunities for students to actively develop critical thinking skills. The method used is library research, which is a research approach related to collecting and analyzing information from various published sources. The data analysis technique used is qualitative descriptive analysis technique. With a qualitative approach, the researcher intends to describe how the cooperative learning model works. After that, the researcher revealed the results of the review by describing the results of the research by telling the actual situation. This class action research was conducted at SDN 14 Selat Penuguan by using three cycles to achieve research objectives, each cycle was carried out in three meetings. Research using this cooperative learning model from the ability to think critically cycle I, cycle II, cycle III has increased. critical thinking is an intellectual thinking process that involves analysis, evaluation, and assessment of information and argumentation. Critical thinking also includes the ability to identify weaknesses and strengths in arguments, compare perspectives, which is one way to improve critical thinking by using cooperative learning methods.